2015
DOI: 10.4028/www.scientific.net/amm.723.825
|View full text |Cite
|
Sign up to set email alerts
|

Optical Breakdown on the Inclined Target: The Features of the Erosive Plume Formation

Abstract: For oblique incidence of laser radiation on the target, the breakdown of air and erosive jet are separated in time and space. The electron density is higher in the air breakdown area while Al I density is higher in an erosive plume area. We also defined plasma expansion mechanism and estimate the time of erosive plume formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Consequently, the angle between the resulting line and the sample normal was considered as the expansion angle. According to previous reports, this expansion angle corresponds to the absorption wave 15 . The expansion angle of the ablated sample material was inferred from the spectrally resolved tomographic reconstructions.…”
Section: Plasma Characterizationsupporting
confidence: 57%
See 1 more Smart Citation
“…Consequently, the angle between the resulting line and the sample normal was considered as the expansion angle. According to previous reports, this expansion angle corresponds to the absorption wave 15 . The expansion angle of the ablated sample material was inferred from the spectrally resolved tomographic reconstructions.…”
Section: Plasma Characterizationsupporting
confidence: 57%
“…Thus, it is likely that only the expansion of the absorption wave has been observed. On the contrary, according to spectrally resolved studies, the majority of the sample material's emission can be observed along the normal of the sample surface 15,16 despite the plasma expanding along the incident laser pulse.…”
Section: Introductionmentioning
confidence: 99%